Pourquoi je ne publie(rai) plus (jamais) dans des revues scientifiques. - Olivier Ertzscheid (Tracés, 2018)
This blog post explains why a researcher in Information and Communication Sciences no longer wish to publish articles in academic journals. Underlying the shortcomings of academic peer-review, as well as the relative confidentiality of communication and the public cost of academic publishing, the delays for effective publishing, he suggests to have become the champion of open archive and open access, in better capacity to fulfill the mission of publicizing scientific work.